(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Companies Act 2016 is now the legal framework that regulates the law and practices of companies that are incorporated under this Act. It repealed the previous Companies Act 1965 after five decades later. The CA 2016 came into force on 31st January 2017 and became operational on that date. It comprises 620 sections and 13 schedules and it is the result of the strenuous study by the Corporate Law Reform Committee (“CLRC”) which was established by the Companies Commission of Malaysia and had undertaken the review of the 1965 Act. CLRC was part of the CCM’s strategic direction initiatives formulated in 2003 to develop a dynamic and conducive environment for business in Malaysia.The 2016 Act has brought in the modernizing of Insolvency Law by introducing Corporate Rescue Mechanisms to revive financially troubled companies, restructuring the concept of scheme of arrangements between a company and its creditors and refining the role of receivers/receivers & managers. The 2016 Act has also decoupled the requirement for an approved liquidator to be an approved auditor as under the old Act, it requires the approved liquidator to hold an audit licence before he or she can apply for a liquidator’s licence.Under Section 433(3) of CA 2016, any person who is a member of a recognised professional body may apply to the Minister of Finance to be approved as a liquidator. The Minister of Finance may approve such a person as a liquidator if he is satisfied with the experience and capacity of the person and upon payment of the prescribed fee by such a person. The minister, in consultation with the Minister of Finance has prescribed Malaysian Institute of Accountants (“MIA”) and Malaysian Institute of Certified Public Accountants (“MICPA”) as recognised professional bodies with effect from 15th March 2018.According to the statistics of liquidators as at 31 December 2018 compiled by the MIA, there are 197 Chartered Accountants who are in possession of liquidators’ licences. Out of these 197, a total of 143 or 73% are aged 60 to 81 and above. This means that when these approved liquidators retire at age 60 and above, there are 54 approved liquidators left who may not be in active practice. The statistics revealed that there is an acute shortage of approved liquidators in Malaysia. These liquidators would not be able to cope with handling the huge number of companies that have gone into compulsory liquidation, which at present stand at 42,406 from 2009 to 2019 of which 25,950 cases are being handled by the Official Receiver. With the limited resources at the Official Receiver’s offices nationwide, it proves that it would take a long time for the Official Receiver to complete the winding up of the affairs of the wound up companies.The 2016 Act has opened the door for a chartered accountant of MIA or Certified Public Accountant to apply directly for liquidator’s licence without the need to possess an audit licence 1st. This paper will deal with the various types of appointment which an insolvency practitioner can act, the basis of their remuneration, the authority that supervises their conduct in handling the affairs of the wound up companies, the various networks which the insolvency practitioner can build their network and the areas in which the industrial revolution 4.0 has disrupted businesses which can have an impact on the values of the property or assets to be disposed of.